1992
DOI: 10.1017/s0031182000061710
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat distribution and coexistence of Dactylogyrus species (Monogenea) on the gills of roach

Abstract: S U M M A R YThe Dactylogyrus fauna was studied from the gills of 293 roach between February 1988 and April 1989. Roach were caught from three interconnected lakes in Central Finland. Nine Dactylogyrus species were found. Of these the seven most abundant were used for studying the abundance of species on different gill-arches, niche breadth and niche overlap between the species. It was found that all species had a species-specific preference for certain gill-arches. The total abundances of all the species went… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…In the same way, the increase in temperature during the warm season accelerated development of thermophilic dactylogyrids (Chubb 1977, Koskivaara et al 1992, as observed for D. formosus after 4 d of holding. According to Prost (1963), the temperature optimum for dactylogyrid reproduction (D. anchoratus) is 23°C.…”
Section: Discussionsupporting
confidence: 53%
“…In the same way, the increase in temperature during the warm season accelerated development of thermophilic dactylogyrids (Chubb 1977, Koskivaara et al 1992, as observed for D. formosus after 4 d of holding. According to Prost (1963), the temperature optimum for dactylogyrid reproduction (D. anchoratus) is 23°C.…”
Section: Discussionsupporting
confidence: 53%
“…Parasites, and specifically ectoparasites, seem to be an interesting model for such studies (Rohde 1991;Koskivaara et al 1992), as the hosts can be considered as the available islands . Monogenean ectoparasite communities are a useful ecological model for investigating the structure and organisation of communities (Rohde 1979;Morand et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Marine fishes are useful models to investigate questions dealing with ecology of parasite community structure (Rohde 1989, Holmes 1990. Gill ectoparasites are increasingly used to investigate the evolutionary significance of extrinsic or intrinsic factors of niche restriction such as intra-or interspecific competi-tion, reinforcement of reproductive barriers and en-hancement of the chance to mate (Rohde 1977, 1979, 1980, 1989, 1994, Ramasamy et al 1985, Koskivaara et al 1992, Sharples and Evans 1995, Lo and Morand 2000. In a recent paper, Geets et al (1997), following Rohde's hypothesis (1991), suggested that interspecific competition be of secondary importance for microhabitat choice whereas intraspecific factors such as mating process and reinforcement of reproductive barriers affect exploitation of gill-space by parasites.…”
mentioning
confidence: 99%